Comparison of resting heart rate measured using a cardiac monitor and an oscilometric device in adolescents: Analysis of sensitivity and specificity - Zanuto, Edner F. [UNESP]; Saraiva, Bruna C. [UNESP]; Vanderlei, Luiz C.M. [UNESP]; Júnior, Paulo Costa [UNESP]; Agostinete, Ricardo R. [UNESP]; Zanuto, Everton A.C. [UNESP]; Fernandes, Rômulo A. [UNESP]; Christofaro, Diego G.D. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2016)
Study design: Experimental study Objectives: To assess the consistency and efficiency of an oscillometric device for measuring resting heart rate in adolescents. Methods: Data from adolescents of both sexes aged between 10 and 15 years were analyzed. Weight was measured using a digital scale and height, a stadiometer. Body mass index was calculated by dividing body weight by the height squared. The resting heart rate was measured with a heart rate monitor and an oscillometric device for measuring blood pressure. The mean and standard deviation were used to describe the characteristics of the sample. Pearson's correlation was used to examine the relationship between the two devices. Reproducibility was assessed by the intraclass correlation coefficient and efficiency by the receiver operating characteristic curve. Results: Moderate/high correlations were found (r=0.80) between the heart rate monitor and oscillometric device. The intraclass correlation coefficient showed values of 0.88 (0.66-0.96) for girls and 0.90 (0.82-0.95) for boys. The sensitivity was 70.0 (34.8-93.3) and 80.4 (28.4- 99.5) and the specificity 86.6 (69.3-96.2) and 90.0 (55.5-99.7) for boys and girls respectively. Conclusion: The oscillometric device showed good reproducibility and moderate sensitivity and specificity for measuring resting heart rate in adolescents.
Keywords: Adolescent; Blood pressure monitors; Heart rate